Chronic Renal Failure Secondary to Unrecognized Neurogenic Bladder in A Child with Myelodysplasia - AHMED, Shameem; PAUL, Siba Prosad (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Ahmed S, Paul SP. Chronic Renal Failure Secondary to Unrecognized Neurogenic Bladder in A Child with Myelodysplasia. Iran J Child Neurol. Spring 2017; 11(2):78-81. Abstract Myelodysplasia includes a group of developmental anomalies resulting from defects that occur during neural tube closure. Urological morbidity in patients with myelodysplasia is significant and if not treated appropriately in a timely manner can potentially lead to progressive renal failure, requiring dialysis or transplantation. We report the case of a 13-year old girl with neurogenic bladder who presented chronic renal failure secondary to lipomyelomeningocele with retethering of cord. She was managed with urinary indwelling catheterization until optimization of renal function and then underwent detethering of cord with excision and repair of residual lipomeningomyelocele. Her renal parameters improved gradually over weeks and then were managed on self clean intermittent catheterization. The case emphasizes the need for considering rethering of spinal cord in children with myelodysplasia where symptoms of neurogenic bladder and recurrent urinary tract infections occur. References 1. Favazza TF. Myelodysplasia and Neurogenic Bladder Dysfunction. 2014. Available at http://emedicine. medscape.com/article/1015695-overview (accessed 30th August 2016) 2. Larijani FJ, Moghtaderi M, Hajizadeh N, Assadi F. Preventing Kidney Injury in Children with Neurogenic Bladder Dysfunction. Int J Prev Med. 2013;4(12):1359- 64. 3. de Azevedo RV, Oliveira EA, Vasconcelos MM, et al. Impact of an interdisciplinary approach in children and adolescents with lower urinary tract dysfunction (LUTD). J Bras Nefrol. 2014;36(4):451-9. 4. Elliott SP, Villar R, Duncan B. Bacteriuria management and urological evaluation of patients with spina bifida and neurogenic bladder: a multicenter survey. J Urol. 2005;173(1):217-20. 5. Danforth TL, Ginsberg DA. Neurogenic lower urinary tract dysfunction: how, when, and with which patients do we use urodynamics? Urol Clin North Am. 2014;41(3): 445-52. 6. Seki N, Masuda K, Kinukawa N, Senoh K, Naito S. Risk factors for febrile urinary tract infection in children with myelodysplasia treated by clean intermittent catheterization. Int J Urol. 2004;11(11):973-7. 7. Kochakarn W, Ratana-Olarn K, Lertsithichai P, Roongreungsilp U. Follow-up of long-term treatment with clean intermittent catheterization for neurogenic bladder in children. Asian J Surg. 2004; 27(2):134-6. 8. Obara K, Mizusawa T, Isahaya E, et al. Efficacy of Clean Intermittent Catheterization for Urinary Incontinence in Children with Neurogenic Bladder Dysfunction Secondary to Myelodysplasia. Low Urin Tract Symptoms. 2010;2(2):100-5.